Records of the Judicial Committee of the Privy Council (as filmed by the AJCP) [M1586-M1614] - Great Britain. Privy Council. Judicial Committee; Australian Joint Copying Project; National Library of Australia; State Library of New South Wales (Canberra : Australian Joint Copying Project, 1950)
Printed papers prepared for cases heard by the Judicial Committee of the Privy Council in London on appeal from courts in Australia, New Zealand and Fiji. All the papers are on the pre-1873 cases were filmed, including the often lengthy background papers which contained evidence and records of proceedings in the lower courts. For the 1873-1972 period only the written cases for the appellants and respondents were copied, together with judgements that had not been reported in the published law reports. In addition to the appeal cases, reel M1586 contains papers on two constitutional disputes in the 19th century which were referred to the Privy Council by Australian governments.
Filmed as part of the Australian Joint Copying Project by the National Library of Australia and the State Library of New South Wales.
National Library of Australia holds microfilm master.
Australian Joint Copying Project handbook. Part 8 : Miscellaneous [M series]
Australian Joint Copying Project miscellaneous series M1586-1614.
Also available online
Microfilm copy of originals held by the Judicial Committee of the Privy Council, Downing Street, London.
Keywords: Great Britain. -- Privy Council. -- Judicial Committee -- Archives; Court records -- Great Britain; Courts -- Great Britain -- Cases; Constitutional law -- Australia -- Cases